Lagrangian planes in hyperkähler varieties of K3(n)-type - Oberdieck, Georg (Mathematische Zeitschrift, 2025)
Jieao Song recently conjectured a formula for the class of a Lagrangian plane on a hyperkähler variety of K 3[n]-type in terms of the class of a line on it. We give a proof of this conjecture if the line class is primitive.
Gesehen am 25.08.2025
Im Text ist "n" in eckiger Klammer hochgestellt